Building an RPG with Unity 2018 - Karamian, Vahé (Packt Publishing, 2018)
Unity is one of the most cutting-edge game engines in the world. This comprehensive guide on building some core features of an RPG with Unity teaches you techniques used in developing modern games. The book will mainly focus on the strategy, planning and the implementation of the code. By the end of the book, you will be able to build upon the ... Cover – Title Page – Copyright and Credits – Dedication – Packt Upsell – Contributors – Table of Contents – Preface – Chapter 1: What is an RPG? – A brief history of the genre – Characteristics of an RPG – Story and setting – A glimpse of a cRPG story – Exploration and quests – A glimpse at our exploration and quests – Inventory system – Character attributes and actions – Experience and leveling – Combat system – User interaction and graphics – Existing or upcoming RPG games – MU Legend – Titan Siege – Citadel: Forged with Fire – Cyberpunk 2077 – Patterns in RPG – Terminology – Contest tree – Last Man Standing – Negotiated Contest – Summary – Chapter 2: Planning the Game – Building our RPG – The story of the Zazar dynasty – Backstory – Exploration and quests – Awakening – The village – Broken forest - the horizon – The kingdom – Asset inventory – Environment assets – Medieval Environment Pack – Terrain Toolkit 2017 – Nature Starter Kit 2 – Character assets – Barbarians – Orcs – Villagers – Free Assets – Level design – Setting the stage – Terrain toolkit in a nutshell – The Awakening – Using the terrain model – Using a custom toolkit – Skybox – Testing the level – Creating the main menu – Creating the GameMaster script – Summary – Chapter 3: RPG Character Design – Character definitions – Character assets – Base character class attributes – Character states – Character model – Default character models – Barbarian – Villager – Orc – Let's get started – Rigging your model – Character motion – Animator Controller – Animation states – Character controller – Modification to animations – Inverse Kinematics – Setting the animation curve – Summary – Chapter 4: The Game Mechanics – Customizing the player character – Customizable parts – User interface. The code for character customization – Preserving our character state – Recap – Non-player characters – Non-player character basics – Setting up the non-player character – NPC Animator Controller – NPC Attack – NPC AI – PC and NPC interaction – Summary – Chapter 5: GameMaster and Game Mechanics – GameMaster – Managing game settings and audio – Managing scenes – Improving GameMaster – Level controller – Audio controller – Player data management – PC class enhancements – Character customization class update – Changes to the game level controller – Testing – Summary – Chapter 6: Inventory System – Designing an inventory system – Weighted inventory – Determining item types – Creating an inventory item – Creating the prefab – Adding an inventory item agent – Inventory items defined as prefabs – Designing an inventory interface – Creating the inventory UI framework – Designing a dynamic item viewer – Adding a scroll view – Adding elements to PanelItem and Scroll View – Adding txtItemElement dynamically – Building the final inventory item UI – Integrating the UI with the actual inventory system – Hooking the category buttons and displaying the data – Testing the inventory system – Inventory items and the player character – Applying inventory items – How it looks – Summary – Chapter 7: User Interface and System Feedback – Designing a heads-up display – HUD basics – Our design – HUD framework – Completing our HUD design – Character info panel – Active inventory items panel – Special items panel – Integrating the code – Enemy stats in the HUD – NPC stats user interface – Creating the NPC canvas – NPC taking a hit – Enhancing the code – Summary – Chapter 8: Multiplayer Setup – Challenges of a multiplayer game – Initial multiplayer game – Fundamental networking components
Keywords: Computer games-Programming; Computer games-Design; Unity (Electronic resource); Spiel-Engine; Listenprogrammgenerator; Computerspiel; Rollenspiel